Prevalence of hemoplasmas and Bartonella species in client-owned cats in Beijing and Shanghai, China - YU, Yonglan; LOU, Yinying; ZHANG, Zhixuan; ZHANG, Yingxin (Journal of Veterinary Medical Science, 2021)
A year-round molecular epidemiological survey (2017 to 2018) was conducted on three hemoplasmas and two Bartonella species with zoonotic potential in client-owned cats in Beijing and Shanghai. Among 668 specimens, the overall hemoplasma-positive rate was 4.9% (3.4% for Candidatus Mycoplasma haemominutum, 0.9% for Mycoplasma haemofelis and 1.2% for Candidatus Mycoplasma turicensis). The overall Bartonella-positive rate was 8.5% (4.8% for B. henselae and 4.3% for B. clarridgeiae). Age, breed, ectoparasiticide use and stray history, but not city, season and gender, were significantly associated with the positive rates of one or more pathogens. This is also the first report on the prevalence of Candidatus Mycoplasma turicensis in cats in China.